Combined Clinical, Epidemiological, and Genome-Based Analysis Identified a Nationwide Outbreak of Burkholderia cepacia Complex Infections Caused by Contaminated Mouthwash Solutions - Bender, Jennifer K.; Haller, Sebastian; Pfeifer, Yvonne; Hogardt, Michael; Hunfeld, Klaus-Peter; Thuermer, Andrea; Zanuzdana, Arina; Werner, Markus; Kunz, Bernd; Eisenberger, David; Pfennigwerth, Niels; Kempf, Volkhard A. J.; et al. (Open Forum Infectious Diseases, 2022)
Background In September 2018, Burkholderia cepacia complex (BCC) infections in 3 patients associated with exposure to a mouthwash solution (MWS) were reported to the Robert Koch Institute (RKI). As the product was still on the market and the scale of the outbreak was unclear, a nation-wide investigation was initiated. Methods We aimed to investigate BCC infections/colonizations associated with MWS. Hospitals, laboratories, and public health services were informed that BCC isolates should be sent to the RKI. These isolates were typed by pulsed-field gel electrophoresis (PFGE) and whole-genome sequencing (WGS) including development of an ad hoc core genome MLST (cgMLST) scheme. Results In total, 36 patients from 6 hospitals met the case definition, the last patient in November 2018. Twenty-nine isolates from 26 of these patients were available for typing. WGS analysis revealed 2 distinct cgMLST clusters. Cluster 1 (Burkholderia arboris) contained isolates from patients and MWS obtained from 4 hospitals and isolates provided by the manufacturer. Patient and MWS isolates from another hospital were assigned to cluster 2 (B. cepacia). Conclusions The combined clinical, epidemiological, and microbiological investigation, including whole-genome analysis, allowed for uncovering a supraregional BCC outbreak in health care settings. Strains of B. arboris and B. cepacia were identified as contaminating species of MWS bottles and subsequent colonization and putative infection of patients in several hospitals. Despite a recall of the product by the manufacturer in August 2018, the outbreak lasted until December 2018. Reporting of contaminated medical products and recalls should be optimized to protect patients.
CRIS-Team WoS Importer:2022-04-29
Keywords: Burkholderia arboris; outbreak; clonal transfer; mouthwash solution; medical device

First report of the new emerging global clone ST1193 among clinical isolates of extended-spectrum beta-lactamase (ESBL)-producing Escherichia coli from Germany - Valenza, Giuseppe; Werner, Markus; Eisenberger, David; Nickel, Silke; Lehner-Reindl, Verena; Hoeller, Christiane; Bogdan, Christian (Journal of Global Antimicrobial Resistance, 2019)
Objectives: Sequence type 1193 (ST1193) is a new emerging global clone of Escherichia coli. The main goal of this study was to determine the prevalence and molecular characteristics of ST1193 among clinical isolates of extended-spectrum beta-lactamase (ESBL)-producing E. coli from University Hospital of Erlangen, Germany.
CRIS-Team WoS Importer:2019-07-09

Whole-genome analysis of vancomycin-resistant Enterococcus faecium causing nosocomial outbreaks suggests the occurrence of few endemic clonal lineages in Bavaria, Germany - Eisenberger, David; Tuschak, Christian; Werner, Markus; Bogdan, Christian; Bollinger, Thomas; Hossain, Hamid; Friedrich, Petra; Hussein, Ziyad; Pöhlmann, Christoph; Würstl, Benjamin; Nickel, Silke; Lehner-Reindl, Verena; et al. (Journal of Antimicrobial Chemotherapy, 2020)
OBJECTIVES: Infections caused by vancomycin-resistant Enterococcus faecium (VREfm) represent a major public health concern due to limited treatment options. Among invasive isolates of VREfm, ST117, ST80 and ST78 represent the most frequently detected STs by MLST in Germany. In this study, we investigated the genetic diversity of isolates of VREfm recovered from different nosocomial outbreaks in Bavaria, Germany, by WGS. METHODS: Between January 2018 and April 2019, 99 non-replicate isolates of VREfm originating from nosocomial outbreaks at eight different hospitals in Bavaria were investigated for genetic diversity by WGS. In detail, complex types (CTs) were identified by core-genome MLST. Furthermore, an SNP analysis was performed for all VREfm strains. RESULTS: Most of the isolates of this study (76%) belonged to three major clonal groups, which occurred in at least three hospitals: ST80/CT1065 vanB (n = 45; six hospitals), ST117/CT71 vanB (n = 11; four hospitals) and ST78/CT894like vanA (n = 19; three hospitals). Moreover, isolates of the predominant lineage ST80/CT1065 vanB showed a maximum difference of 36 SNPs as revealed by SNP analysis. CONCLUSIONS: Whole-genome analysis of VREfm causing nosocomial outbreaks suggests the occurrence of few endemic clonal lineages in Bavarian hospital settings, namely ST80/CT1065 vanB, ST117/CT71 vanB and ST78/CT894like vanA. Further studies are needed for a better understanding of the factors affecting the successful spread of the above-mentioned lineages.
CRIS-Team Scopus Importer:2020-06-02